Posterior Vaginoplasty With Perineoplasty: A Canadian Experience With Vaginal Tightening Surgery - Austin, Ryan E (Aesthet Surg J Open Forum, 2019)
Following vaginal trauma, most commonly vaginal delivery, women may experience vaginal laxity as a result of local tissue stretching and separation of the pelvic floor musculature. In addition to this generalized sensation of laxity, women may complain of decreased sexual satisfaction, gaping of the perineum, and excessive vaginal secretions. Since 2014, the authors have used a posterior vaginoplasty with perineoplasty technique for the surgical management of vaginal laxity. To date, the authors have performed surgical vaginal tightening in 30 consecutive patients and found that the posterior vaginoplasty with perineoplasty technique has allowed us to achieve reproducible outcomes with no postoperative complications. This article will review the authors’ approach to patients presenting for surgical vaginal tightening and the authors’ experience to date, including our preoperative screening, perioperative management, and detailed steps of the procedure.